miR-146a Enhances the Oncogenicity of Oral Carcinoma by Concomitant Targeting of the IRAK1, TRAF6 and NUMB Genes - Hung, Pei-Shi; Liu, Chung-Ji; Chou, Chung-Shan; Kao, Shou-Yen; Yang, Cheng-Chieh; Chang, Kuo-Wei; Chiu, Ting-Hui; Lin, Shu-Chun (PLOS ONE, 2013)
MicroRNAs are short non-coding RNAs that regulate gene expression and are crucial to tumorigenesis. Oral squamous cell carcinoma (OSCC) is a prevalent malignancy worldwide. Up-regulation of miR-146 has been identified in OSCC tissues. However, the roles of miR-146 in carcinogenesis are controversial as it is suppressive in many other malignancies. The present study investigated the pathogenic implications of miR-146a in oral carcinogenesis. Microdissected OSCC exhibits higher levels of miR-146a expression than matched adjacent mucosal cells. The plasma miR-146a levels of patients are significantly higher than those of control subjects; these levels decrease drastically after tumor resection. miR-146a levels in tumors and in patients’ plasma can be used to classify OSCC and non-disease status (sensitivity: >0.72). Exogenous miR-146a expression is significantly increased in vitro oncogenic phenotypes as well as during xenograft tumorigenesis and OSCC metastasis. The plasma miR-146a levels of these mice parallel the xenograft tumor burdens of the mice. A miR-146a blocker abrogates the growth of xenograft tumors. miR-146a oncogenic activity is associated with down-regulation of IRAK1, TRAF6 and NUMB expression. Furthermore, miR-146a directly targets the 3′UTR of NUMB and a region within the NUMB coding sequence when suppressing NUMB expression. Exogenous NUMB expression attenuates OSCC oncogenicity. Double knockdown of IRAK1 and TRAF6, and of TRAF6 and NUMB, enhance the oncogenic phenotypes of OSCC cells. Oncogenic enhancement modulated by miR-146a expression is attenuated by exogenous IRAK1 or NUMB expression. This study shows that miR-146a expression contributes to oral carcinogenesis by targeting the IRAK1, TRAF6 and NUMB genes.